Sleep hygiene for optimizing recovery in athletes: Review and recommendations - Vitale, K. C.; Owens, R.; Hopkins, S. R.; Malhotra, A. (International Journal of Sports Medicine, 2019)
For elite athletes who exercise at a high level, sleep is critical to overall health. Many studies have documented the effects of sleep deprivation in the general population, but few studies exist regarding specific effects in the athlete. This review summarizes the effects of sleep deprivation and sleep extension on athletic performance, including reaction time, accuracy, strength and endurance, and cognitive function. There are clear negative effects of sleep deprivation on performance, including reaction time, accuracy, vigor, submaximal strength, and endurance. Cognitive functions such as judgment and decision-making also suffer. Sleep extension can positively affect reaction times, mood, sprint times, tennis serve accuracy, swim turns, kick stroke efficiency, and increased free throw and 3-point accuracy. Banking sleep (sleep extension prior to night of intentional sleep deprivation before sporting event) is a new concept that may also improve performance. For sports medicine providers, the negative effects of sleep deprivation cannot be overstated to athletes. To battle sleep deprivation, athletes may seek supplements with potentially serious side effects; improving sleep quality however is simple and effective, benefiting not only athlete health but also athletic performance.